Moving in and out of poverty understanding social mobility from perspectives of the still-poor, Now poor, once--poor, and never poor of Payatas B. Quezon City - Guevara, Marita Concepcion Castro (2008)
Using an interpretive approach, and guided by Giddens' structuration theory and Moser's asset vulnerability framework, this research attempted to listen and learn from the stories of Payatas households about how, in their view, they "remained in poverty," "fell into poverty,""moved out of poverty," or "never experienced poverty," in the period 2002-2007. It also probed their views on the different aspects of poverty and well-being in urban informal settlements, particularly in Payatas. Specifically, the paper asked the following questions: What significant changes have occurred in Payatas since 2002 which have made the lives of Payatas residents either more vulnerable or more secure? How do Payatas residents distinguish various levels of poverty and well-being? From their perspective, did their households "never know poverty." "or" "move out of poverty," or "stay mired in poverty." in the period 2002-2007?How do they, on their own and linking up with others, seek to reduce and mitigate the various risks to which they are exposed? And how do civil society organizations and local and national governance systems promote and/or inhibit transitions out of poverty? in analyzing the research results in Chaper VI, the study sought to show the interaction between the agency of the urban poor, on the one hand (i.e., their management of their household assets), and social structures, on the other (e.g., developments in the economy, government ans societal stance toward the urban poor, civil society efforts). This study concludes that Payatas,as a community, has improved in many ways since 2002. There is a greater access to water, electricity, and telecommunications; more health and educational facilities, and improved quality of instruction; more paved roads; a better-managed and less odorous dump site; and less violence and crime. These community improvements can be attributed to the action of committed barangay and city officials, and representatives of national government agencies; the infusion of assistance from civil society organizations, especially after the July 2000 garbage slide; and not the least efforts of Payatas residents themselves to form neighborhood associations and other peoples' organizations to address their problems and issues, especially those pertaining to land and housing, and the delivery of social services. Notwithstanding these community improvements, the majority (74%) of the 89 Payatas households surveyed in 2007 rated themselves as either "very poor" (8%), "poor" for 2002. That is 76 percent of these same households said that they were either "very poor" (15%), "poor" (25%), or "somewhat poor" (36%) in 2002. According to what the Payatas research participants share, there seem to be six factors hindering urban poor households, "ability to move out of poverty: (1) a large household size; (2)laziness and proclivity to vices; (3) a low educational attainment that deters one from finding a good job, if any at all; (4) unavailability, insufficiency, or insecurity of employment; (5)the rising cost of urban goods and services, without the corresponding increase in wages/salaries/income; and (6) insecurity of land and housing tenure, which may result in demolitions. Some of these factors are aspects of agency for urban poor households (e.g., household size, laziness, vices). Other can be attributed to structural reasons like economic development (e.g., lack of employment, rise in prices) and social and political factors (e.g., low educational attainment, insecurity of tenure/demolitions). The study concludes with recommendations addressed to the urban poor themselves, civil society organizations, and the local, city, and national governments. Moreover, it affirms that the whole point of development is to enable people to participate in the governance of their own lives. For this reason, it underscored the importance of listening to what poor people have to say.